2006
DOI: 10.1021/jf061148q
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Free Radical Transfer in Lipoxygenase I-B-Catalyzed Linoleic Acid−Soybean Protein Interaction by Electron Spin Resonance Spectroscopy (ESR)

Abstract: Effects of lipoxygenase I-B (LOX)-catalyzed oxidation of linoleic acid on soybean proteins was evaluated by electron spin resonance (ESR) and fluorescence spectroscopy in different model systems in the presence or absence of antioxidants. A strong central singlet signal was detected by ESR spectroscopy and identified as the carbon radical (g value range 2.0041-2.0054). A downfield shoulder attributed to the sulfur radical (g value 2.019-2.028) was also observed. The changes in soybean proteins were accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…There is abundant evidence that lipid peroxidation products, which include free radicals, lipid hydroperoxides and reactive aldehyde derivatives, are capable of modifying proteins (Refsgaard, Tsai, & Stadtman, 2000). Previous study in our laboratory indicated that the major mechanism of linoleic acid oxidative damage to soy protein was due to free radical transfer from lipoxygenasecatalyzed oxidized polyunsaturated fatty acid to soy protein (Huang, Yu, et al, 2006). The roles of reactive aldehydes and lipid hydroperoxides in the course of soy protein oxidation are neglected, although primary lipid hydroperoxides easily decompose into reactive aldehydes.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…There is abundant evidence that lipid peroxidation products, which include free radicals, lipid hydroperoxides and reactive aldehyde derivatives, are capable of modifying proteins (Refsgaard, Tsai, & Stadtman, 2000). Previous study in our laboratory indicated that the major mechanism of linoleic acid oxidative damage to soy protein was due to free radical transfer from lipoxygenasecatalyzed oxidized polyunsaturated fatty acid to soy protein (Huang, Yu, et al, 2006). The roles of reactive aldehydes and lipid hydroperoxides in the course of soy protein oxidation are neglected, although primary lipid hydroperoxides easily decompose into reactive aldehydes.…”
Section: Introductionmentioning
confidence: 92%
“…Soy protein oxidative damage is associated with content of residual lipids and activity of lipoxygenase in commercial low denatured defatted soybean flours . Lipoxygenase -catalyzed linoleic acid peroxidation products were highly reactive substances that could change the structural characteristics of soy protein according to a free radical transfer mechanism (Huang, Yu, Hua, & Qiu, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al 2 found that the oxidation extent of soy protein was affected by the content of residual lipids and activity of lipoxygenase in commercial low denatured defatted soybean flours. Subsequently, studies revealed that the lipoxygenase‐mediated polyunsaturated fatty acid peroxidation products changed the structural characteristics of soy protein 3. Further studies showed that gelling ability of soy protein steadily declined as oxidation extent of soy protein increased 4…”
Section: Introductionmentioning
confidence: 99%
“…The reported lipid contents of laboratory prepared ISP samples are slightly lower at 3.5% to 4.0%. Because free radicals have been shown to occur in various types of proteins as a result of exposure to oxidized lipids (Schaich and Karel 1976; Huang and others 2006), the contribution of the naturally‐occurring lipids in ISP samples toward the development of metastable radicals was investigated. To accomplish this, the remaining lipids in commercial “defatted” flour were exhaustively extracted with chloroform/methanol.…”
Section: Resultsmentioning
confidence: 99%